Family-Supportive Work Environment and Employee Work Behaviors: An Investigation of Mediating Mechanisms. (March 2013) - Aryee, Samuel; Chu, Chris W. L.; Kim, Tae-Yeol; Ryu, Seongmin
This study examined psychological mechanisms that underpin the relationships between perceived organizational family support (POFS) and a family-supportive supervisor (FSS) on employee work behaviors. Based on data from employed parents and their supervisors (N = 230) in 12 South Korean organizations, structural equation modeling results revealed three salient findings: (1) POFS and FSS are indirectly related to contextual performance through control over work time, (2) FSS is indirectly related to both contextual performance and work withdrawal through organization-based self-esteem (OBSE), and (3) control over work time is indirectly related to the two work outcomes through OBSE. The authors interpret these findings as indicating support for the focus on informal workplace family support and the need for research to examine the psychological resources they engender if we are to understand why these forms of support have their demonstrated outcomes.